Rate‐limiting processes of tau aggregate accumulation in Alzheimer's disease. (December 2021) - Meisl, Georg; Zuo, Yukun; Allinson, Kieren; Rittman, Timothy; DeVos, Sarah L.; Sanchez, Justin S; Xu, Catherine K.; Duff, Karen E.; Johnson, Keith A.; Rowe, James B.; Hyman, Bradley T.; Knowles, Tuomas; et al.
Abstract: Background: Both the replication of tau aggregates and their spreading throughout the brain are implicated in the progression of Alzheimer's disease (AD). However, the rates of these processes are unknown and the identity of the rate‐determining process in humans has therefore remained elusive. Using a mathematical framework based on chemical kinetics, we are able to answer these questions by analysis of experimental data from AD patients. Method: Our minimal mathematical model of aggregate spreading and replication enables us to determine the rates of spreading and replication from measurements of tau seeds and aggregates across brain regions. Simulations based on this model show clearly distinct patterns of tau distributions when the behaviour is limited by either replication or spreading (Fig 1). We analysed several already existing datasets from in vitro seeding experiments, tau pathology in P301S transgenic mice, and histochemical post‐mortem as well as 2‐year longitudinal tau PET data in humans (Fig 2). Result: Across mice and human data, we found that the overall rate of accumulation of tau in cortical regions is limited not by the rate of tau spreading between brain regions but by the rate of local replication within a brain region. In human post‐mortem data, low levels of tau seeds were present already throughout the cortex at Braak stage 3, where effective replication of those initial seeds rather than inter‐regional spreading was the rate limiting factor for further tau accumulation. The rate of replication determined from these data corresponds to a doubling of the number of seeds only every ∼5 years, which was well in line with the our analysis of tau accumulation from longitudinal tau PET data in AD patients. This rate is orders of magnitude slower than that measured for purified tau in vitro, quantifying the efficiency of innate cellular mechanisms curtailing tau seed replication. Conclusion: Based on these findings, we believe that limiting local replication constitutes the most promising strategy to control tau accumulation during AD, after Braak stage 2. Our results provide a framework for the determination of the identity and the rates of the key steps controlling disease‐associated aggregation processes within living organisms.